Krishna
0

Step 1:  Take the given question

               (\sec^2 \theta - 1)(\cosec^2 \theta - 1)


Step 2: Find the suitable trigonometric identities to simplify the equation

            NOTE:   \sec^2 \theta - 1 = \tan \theta

                           \cosec^2 \theta - 1 = \cot \theta


Step 3: Substitute the trigonometric identities in the given equation  

            EXAMPLE:  = (\sec^2 - 1)(\cosec^2 - 1)

                                =     \tan \theta \cot \theta

                                =  \tan\theta\ \cdot\frac{1}{\tan\theta}      [since. \cot \theta = \frac{1}{\tan \theta}

                                = 1